HAZARD ANALYSIS CRITICAL CONTROL POINT (HACCP) CERTIFICATION OF MICRO AND SMALL SCALE FOOD COMPANIES IN THE PHILIPPINES - Teves, Y Karen (MATTER: International Journal of Science and Technology, 2016)
A review of the country’s micro and small scale food companies revealed that Hazard Analysis Critical Control Point (HACCP) implementation and certification is hindered due to common issues problems and gaps also experienced by some neighboring countries such as limited financial capability, lack of prerequisite program such as hygiene and sanitation in the factory, limited HACCP knowledge and technical competence, proper training, lack of external support from the government and industry associations, management problems like commitment, motivation, and interest in the long-term benefits of HACCP to the company, and lack of government infrastructure and support. Initiatives done by the government to assist small-scale food industries through the Department of Trade and Industry Accreditation Program is one way to encourage voluntary HACCP certification in the food industry. Other HACCP interventions done by the government were cited. Challenges and problems encountered should never hinder the small scale companies’ aim to upgrade its food safety systems. With adequate knowledge and expertise, strong government support and commitment, the companies’ will and interest to adjust to EU and US food legislation, HACCP implementation in small-scale food companies will be achieved and will open avenues to product quality improvement, ensured consumer protection, export opportunities and profit maximization.